'Active & Safe Central': development of an online resource for the prevention of injury in sport and recreational activity. Issue 6 (14th May 2019) - Richmond, Sarah A; Black, Amanda M; Jacob, John; Babul, Shelina; Pike, Ian
Abstract : Background: Sport and recreation related injuries exert a significant cost on the healthcare system. As prevention researchers and practitioners, we have a responsibility to provide guidance towards prevention to those who participate in sport and recreation, and those that coach, treat and parent children that participate. The objective of this project was to use an integrated knowledge translation approach to develop an end user-driven digital platform that provides injury prevention information and resources across 51 sport and recreational activities. Design: We used an integrated knowledge translation approach to scope and develop an online sport and recreational injury prevention resource. A project team was formed that included end users—coaches, parents and athletes, injury researchers and practitioners, as well as members of a digital design team. All members of the project team informed the development process, including a review of literature and existing resources, the translation of evidence and development of the platform. At all stages of development, members of the project team cocreated knowledge for the tool, including forming the research questions, the approach, feasibility and development of outcomes. Conclusion: The 'Active & Safe Central' (https://activesafe.ca/ ) platform provides web-based sport injury and prevention information. This user-friendly, web and mobile accessible platform can increase the reach, awareness and implementation of prevention programming in sport and recreational activity.